The Psychometric Properties of the Norwegian version of Olweus Questionnaire on bullying for pupils (OBVQ/OBVQ-R) - Solberg, Mona; Martinussen, Monica (PsykTestBarn, 2021)
Description: The Olweus questionnaire on bullying for pupils was developed in the 1980’s and is used for studying bullying in schools based on their own reports. In Norway it is primarily being used in grades 4 -7 (primary grades) and grades 8 – 10 (lower secondary grades). The questionnaire form was developed in Norwegian and has been translated into several languages, including English: The Olweus Bully-Victim Questionnaire (OBVQ; Olweus, 1986) and The Revised Olweus Bully/Victim Questionnaire (OBVQ-R; Olweus, 1996). The most employed questions are the two global questions on bullying and two scales based on 7-9 questions on various forms of bullying. The copyright to using the questionnaire in Norway is owned by The Regional Centre for Child and Youth Mental Health and Child Welfare, NORCE Norwegian Research Centre AS. Literature search: The literature search resulted in 15 Norwegian articles (14 independent studies) and 6 Swedish/Danish articles (5 independent studies). Psychometrics: The reliability of the two single questions was not investigated, but for the two scales the internal consistency was found to be good. There are no Norwegian norms, but several very large prevalence studies have been carried out using the two global questions. There are no norm data available for the two scales. The results indicate that the construct validity of the two single questions and the scales are good, but the data base for the scales is much smaller compared to the two single questions. Conclusion: There is good documentation of the test's construct validity, but there is a partial lack of studies of the test's reliability. The two global questions seem suitable for estimating the prevalence of bullying in schools and other larger units, and for classifying children and young people into four groups which describe their self-perceived role or position in bullying situations. No separate norm studies have been carried out, but there are results based on large samples for parts of the questionnaire, which may be used as a basis for comparisons in schools and for research purposes.